Inovasi Bilik Sampah Ramah Lingkungan untuk Wilayah Pesisir Batu Licin Laut - Sri Yulianti; Sindi Novela; Nurul Ain; Melany Apriyanti; Dewi Yuniasari; Apnesia Ningsih Sihite; Muhammad Zulfa; Haikal Pranata; Lintar Liony Akbar (BADAN PENERBIT STIEPARI PRESS, 2025)
Waste problems in Batu Licin Laut coastal area are becoming more complex along with the increasing community activities. The lack of waste management facilities causes most waste, especially plastic and organic, to accumulate in residential areas and end up polluting the sea. This condition not only degrades coastal ecosystems but also threatens public health, such as the spread of waterborne diseases and contamination of seafood consumed by the local community. If left unmanaged, the long-term impact may lead to a decline in marine biodiversity and hinder the sustainability of local livelihoods, particularly for fishermen who rely on clean waters. As a solution, this study introduces Ecoholic, an eco-friendly waste booth designed to separate organic and non-organic waste. The innovation emphasizes practical and community-based approaches by placing booths in easily accessible public spaces. The research employed a descriptive method consisting of booth design, installation in strategic locations, and community socialization through workshops and demonstrations. Socialization activities encouraged residents to actively participate in waste separation and adopt environmentally friendly habits in their daily routines. The results indicate a significant improvement in community understanding, interest, and behavior toward waste management. People became more aware of the importance of waste segregation and were motivated to maintain cleanliness in their surroundings. The presence of Ecoholic has proven effective in reducing waste accumulation while fostering a cleaner and healthier environment. Furthermore, this innovation demonstrates that simple but well-designed facilities, combined with community empowerment, can provide a sustainable model of waste management. Ecoholic has the potential to be replicated in other coastal areas facing similar waste challenges, contributing to broader environmental preservation and community well-being.